ANALYSIS OF THE CONTRIBUTION OF HOTEL TAX AND RESTAURANT TAX TO LOCAL REVENUE OF BANDUNG DISTRICT DURING COVID-19 PANDEMIC - Mutiara Nur Insani; Sendi Gusnandar Arnan (SEAN Institute, 2023)
The purpose of this study was to determine the growth and contribution obtained from hotel taxes and restaurant taxes to Bandung Regency's Regional Original Revenue during the co-19 pandemic. The research method used is descriptive quantitative research to obtain an objective overview of a condition or phenomenon. The data collection techniques used are by conducting literature studies, documentation and field studies which include observation and interviews. The results of this study indicate that the growth of hotel tax and restaurant tax from 2017-2018 was not successful. Overall the contribution rate of hotel tax and restaurant tax is categorized as very less, because the percentage contribution is very far from the 40% figure. This means that every time there is an increase or decrease in the contribution of hotel and restaurant taxes, local revenue does not necessarily increase or decrease, it could be that local revenue is fixed. Another finding is that the growth rate and contribution of hotel and restaurant taxes to local revenue still do not meet the good criteria, due to low taxpayer awareness, extortion by irresponsible officers, and covid-19. Efforts made by the government to overcome these problems include conducting socialization, increasing cooperation with taxpayers, evaluating the performance of the Bandung Regency Regional Revenue Agency, installing taping boxes and tax incentives.